Theme-Rheme And Thematic Progression Analysis Of Joe Biden’s Speech On Israel-Hamas And Russia-Ukraine Wars - Asep Saepuloh; Ningsih, D. Nurfajrin; Halimah (International Journal of Educational and Life Sciences, 2023)
The study mainly focuses on Theme-Rheme and Thematic Progression in the speech of Joe Biden on Israel-Hamas and Russia-Ukraine Wars. The objective of this study is to examine the type of Theme-Rheme and Thematic Progression pattern found in the speech text. To examine the data, the study employed a qualitative method with a descriptive design. The data is derived from Biden’s speech on the United States’ Response to Israel-Hamas and Russia-Ukraine Wars. The data was analysed using Halliday’s theory (1994, 2004) to analyse the Theme-Rheme and Paltridge, (2006) to analyse the Thematic Progression pattern. Based on the study, it shows that Participant as Topical theme is the most dominant, while, Constant theme is the most dominant in Thematic Progression patterns.